2014
DOI: 10.1002/cphc.201300821
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Design of Complex Emulsions

Abstract: Controllable generation of complex emulsions comprising exceptional features such as several compartments and shape anisotropy is becoming increasingly important. Complex emulsions are attracting great interest due to their significant potential in many applications, including foods, pharmaceuticals, cosmetics, materials, and chemical separations. Microfluidics is emerging as a promising route to the generation of complex emulsions, providing precise control over emulsion shape, size, and compartments. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 86 publications
(58 reference statements)
0
38
0
Order By: Relevance
“…Because complex emulsion properties and functions are related to the droplet geometry and composition, the development of rapid, simple fabrication approaches allowing precise control over the droplets’ physical and chemical characteristics is critical. Significant advances in the fabrication of complex emulsions have been made using a number of procedures, ranging from large-scale, less precise techniques that give compositional heterogeneity using high-shear mixers and membranes 10 , to small-volume but more precise microfluidic methods 11,12 . However, such approaches have yet to create droplet morphologies that can be controllably altered after emulsification.…”
mentioning
confidence: 99%
“…Because complex emulsion properties and functions are related to the droplet geometry and composition, the development of rapid, simple fabrication approaches allowing precise control over the droplets’ physical and chemical characteristics is critical. Significant advances in the fabrication of complex emulsions have been made using a number of procedures, ranging from large-scale, less precise techniques that give compositional heterogeneity using high-shear mixers and membranes 10 , to small-volume but more precise microfluidic methods 11,12 . However, such approaches have yet to create droplet morphologies that can be controllably altered after emulsification.…”
mentioning
confidence: 99%
“…This process is defined as dripping. When the flow rate of either fluid is increased, a wider size distribution droplet is generated, due to the jet formation .…”
Section: Nanoemulsification Process: High‐energy Mechanismmentioning
confidence: 99%
“…This process is defined as dripping. When the flow rate of either fluid is increased, a wider size distribution droplet is generated, due to the jet formation [16,23,24]. Although microfluidizers allow narrower droplet distribution in nanoemulsion than of other emulsifying devices, they have some disadvantages such as high manufacturing costs, channels clogged by solid particles and long emulsification time, which leads to recoalescence of emulsion droplets resulting an increase in the droplet sizes [16,21].…”
Section: Nanoemulsification Process: High-energy Mechanismmentioning
confidence: 99%
“…A microfluidic approach to produce such structures provides high accuracy and precision as emulsions are formed on a drop-by-drop basis, giving high control over size, shell thickness [17,18] and morphology. [19] Reports on the formation of core-shell drops with ultrathin shells are scarce. However, Kim et al [14] demonstrated the formation of such structures (both O/W/O and W/O/W) using a 3D glass capillary-based microfluidic device.…”
Section: Introductionmentioning
confidence: 99%